Carla La Mar, Miss Gay San Jose 1977 posing with Crescent Shalimar and Smokey. - Sahl, Ted (photographer):::Creator::::::::::::
A smiling Miss Gay San Jose 1977, Carla La Mar poses with Crescent Shalimar who is dressed in woman's clothing and Smokey.